Ethnomedicinal and Cytotoxic Activities of Calotropis Procera-A Review - MA, Brunda; MA, Bindhu; Kumar BS, Ashok; A, Mouna; B, Subhashini (Asian Journal of Pharmaceutical Research and Development, 2024)
Plants are major sources of drugs that we use today. One such plant is Calotropis procerawhich can be consider as a home for many phytochemicals. Each part of this plant is enriched with various phytochemicals having its own significance for human life. The phytochemistry of this plant reveals presence of triterpenoids, anthocyanins, flavonoids, cardiac glycosides, cardenolides, α– amyrin, β-myrin, lupeol, β-sitosterol, flavanols, mudarin, resin, a powerful bacteriolytic enzyme calactin, a non-toxic proteolytic enzyme calotropin. The plant exhibits antimicrobial, anthelmintic, anti-inflammatory, analgesic, antipyretic, anticancer, antiangiogenic, immunological, antidiabetic, cardio vascular, hypolipidemic, gastro protective, hepatoprotective, renal protective, antidiarrheal, anti-oxidant, anti-convulsant and wound healing effect. This review is an attempt to stack the phytochemical and pharmacological activities of Calotropis procera shrubs.